THE HEROIC AND PHILOSOPHICAL DIMENSIONS IN J.R.R.TOLKIEN'S MYTHIC VISION (International journal of artificial intelligence, 2025)
This article explores the heroic and philosophical dimensions of J.R.R. Tolkien's mythic vision, focusing on his iconic work The Lord of the Rings and its enduring impact on literature. It examines the multi-layered genre structure of Tolkien's writing, blending mythology, epic, and chivalric romance to address profound themes such as the struggle between Good and Evil. Through a comprehensive approach, the article discusses Tolkien's literary influences, including ancient myths and medieval romance, and how they contribute to the philosophical depth of his work. It also highlights the growing field of "Tolkien Studies" and the evolving understanding of his creative legacy.